Analysis the level of landslide using the ROM scale: a study at the sultan haji ahmad shah polytechnic campus - Ishak, Nur Bazilah binti; Yajid, Suhaimi bin; Ab Rashid, Rozalina binti (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2024)
Landslides are a geomorphological process that commonly occurs in tropical climates. Accordingly, a study has been conducted to determine the level of soil collapsibility in problematic slopes around the Sultan Haji Ahmad Shah Polytechnic campus (POLISAS), Kuantan. A total of 3 problematic slope locations were involved in this study. The ROM scale is used as a basis in determining the level of collapsibility of problematic slopes around the POLISAS campus, Kuantan. The results of the study show that Location 1 has a moderate level of collapsibility and is categorized as sandy silt soil with high plasticity. While the other two slope locations, namely Locations 2 and 3, are categorized as high level of collapsibility and categorized as sandy silt with intermediate plasticity. The texture composition of the soil dominated by sand and silt was found to greatly influence the level of soil collapsibility at each sampling location. Accordingly, several problematic slopes around the campus area that have not been maintained need to be restored immediately to avoid the possibility of large- scale landslides occurring in the future.